A randomized controlled trial comparing conventional and piezosurgery methods in mandibular bone block harvesting from the retromolar region - BAYRAM, FERİT (My University, 2023)
Abstract Background Although piezosurgery is now commonly used for various applications in maxillofacial surgery, its advantages over conventional rotary instruments in terms of postoperative edema, ecchymosis, postoperative morbidity, and prolonged osteotomy time have been questioned. Materials and methods This study aimed to compare the efficiency, postoperative morbidity, and complication rates of piezosurgery and conventional methods in harvesting autogenous ramus grafts. In this randomized controlled trial, 21 patients (32 sides) underwent autogenous graft harvesting from the ramus area, with 16 sites treated using piezosurgery and 16 using the conventional method. The primary outcomes measured were osteotomy time, total operation time, and postoperative morbidity. Complication rates were also evaluated. Results The final analysis encompassed 19 patients, accounting for a total of 30 donor sites, following the exclusion of two patients who were unable to attend the scheduled follow-up visits. A total of 19 patients (30 donor sites) were included in the final analysis. No statistically significant difference was found in the mean osteotomy time between the piezosurgery group (mean: 10.35, SD: 2.74 min) and the conventional group (mean: 8.74, SD: 2.74 min) (95% CI: -3.67 to 0.442, p = 0.119). The total operation time, postoperative pain, and swelling were not significantly different between the two groups (p > 0.05). The complication rates, including wound dehiscence and inferior alveolar nerve exposure, were similar in both groups. Conclusions Piezosurgery can be safely used for harvesting autogenous ramus grafts and does not increase osteotomy or total operation time compared to the conventional method. The postoperative morbidity and complication rates were also similar, indicating that both techniques can be effectively employed in clinical practice. Clinical Trial Registration The protocol was registered on clinicaltrials.gov (ID: NCT05548049, First registration date: 21/09/2022).
Keywords: Diş Hekimliği; Klinik Bilimler; Ağız, Diş-Çene Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Dentistry; Clinical Sciences; Oral, Maxillofacial and Surgery; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry